Measuring the limits of uphill timber skidding with a WOODY 110 forestry tractor - Košir, Boštjan (Zbornik gozdarstva in lesarstva, 2007)
The paper deals with the test results of uphill skidding of wood with a WOODY 110 cable skidder. The aim of the study was to find the limits of uphill skidding in relation to load size, log orientation and the slope. The trial was prepared on a test track of concave shape in the forest and with pre-designed loads of different sizes. The loads were skidded uphill once withbutt-end and then with top-end forward, until the tractor stopped because of the slope. The results show that butt-end forward skidding is more efficient. The difference between maximum loads at specific maximum slopes is almost constant (0.53 t). Proper load formation (butt-end forward if possible)is more important when skidding on steeper slopes.
Keywords: breme; forestry; gozdarstvo; naklon; spravilo lesa; traktorji